Design and Performance Analysis of a Dual-Band Fractal Antenna for Millimeter-Wave 5G Applications - Benkhadda Omaima; Reha Abdelati; Saih Mohamed; Harrou Meryama (ITM Web of Conferences)
This article presents the design of a dual-band antenna operating at 28 GHz and 39 GHz. The antenna is structured in the form of a Cantor set fractal with a ground plane featuring a strategically placed slot, which lowers the frequency of the first band to 28 GHz and introduces a second band at 39 GHz. The antenna dimensions are compact, measuring 5 × 6 × 0.508 mm3, and it achieves a maximum gain of 7 dBi with a high radiation efficiency of 99%. The antenna maintains a stable radiation pattern across both frequency bands, making it suitable for millimeter-wave 5G applications, where high data rates and reliable connectivity are crucial.